Influence of Key Strata on the Gas Downward Leakage Law in Dual-System of Coal Seam - Feng Du; Kun Jiao; Zhanyuan Ma (Geofluids)
In Datong mining area, CO and other harmful gases were discharged from the gob in the Jurassic overburden strata to the panel of Carboniferous coal seam. To this end, panel 8309 of Tongxin coal mine in Datong mining area was taken as the engineering background; the change law of CO concentration in the upper corner of the panel and the law of mining pressure were studied through field measurement, and the influence of periodic movement of key strata on the downward leakage law of harmful gases was analyzed. In this paper, the fracture law of the key strata and fracture development characteristics of overburden strata were further studied by the similar simulation test, and the influence of the periodic movement of the key strata on the pathway formation of gas downward leakage was analyzed. The results show that the main cause of harmful gas downward leakage in the Jurassic gob is through the fracture produced by the fracture of the higher key strata. If the higher key strata fractures in the coal mining in the Carboniferous system, through fracture connecting the Jurassic gob above the open-off cut and the upper part of the panel are formed, and effective pathways for gas downward leakage are generated. The fracture and rotation of the higher key strata are accompanied by the formation and disappearance of the effective pathway for gas downward leakage above the panel. Then the periodic change of harmful gas discharging to the panel is caused and consistent with the law of mining pressure.